Medical Student Motivation to Work in E-learning - Druvmale-Druvleja, Baiba; Alondere, Linda; Vovere, B.; Biteniece, I.; Lure, J.; Taurene, A.; Ozols, V. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Nowadays information technology is widley used in studying process thus enabling students to acquire knowledge in a convenient place and time. It is a novel approach and a challenge for both – the students and the faculty of Latvian University Riga Medical College (LU RMK). In order to provide and develope e-learning environment LU RMK has launched a Project whose main objective is „to develop guidelines and video training materials in the e-environment for students and faculty staff in order to provide a more efficient studying process”. Implementation of the project has been started with a pilot study „Medical students’ motivation to work in e-environment”, designed to explore students’ motivation and factors affecting the work of the e environment. Methods: A pilot study using a quantitative method – a survey. To achieve the goal 209 students have been surveyed in the LU RMK.